Fiscal Monitor, October 2014 : Back to Work: How Fiscal Policy Can Help. (Fiscal Monitor; Fiscal Monitor ;, 2014)
At a time when job creation tops the policy agenda globally, this issue of the Fiscal Monitor explores if and how fiscal policy can do more for jobs. It finds that while fiscal policy cannot substitute for comprehensive reforms, it can support job creation in a number of ways. First, deficit reduction can be designed and timed to minimize negative effects on employment. Second, fiscal policy can facilitate structural reforms in the labor market by offsetting their potential short term costs. And third, targeted fiscal measures, including labor tax cuts, can help tackle challenges in specific segments of the labor market, such as youth and older workers.